Paeonol Attenuates Hepatic Ischemia/Reperfusion Injury by Modulating the Nrf2/HO-1 and TLR4/MYD88/NF-κB Signaling Pathways - Mohamed A. Morsy; Yasmine F. Ibrahim; Sara Mohamed Naguib Abdel Hafez; Nagwa M. Zenhom; Anroop B. Nair; Katharigatta N. Venugopala; Pottathil Shinu; Seham A. Abdel-Gaber (Antioxidants, 2022)
Hepatic ischemia/reperfusion (HIR) is the most common type of liver injury following several clinical situations. Modulating oxidative stress and inflammation by Nrf2/HO-1 and TLR4/MYD88/NF-κB pathways, respectively, is involved in alleviating HIR injury. Paeonol is a natural phenolic compound that demonstrates significant antioxidant and anti-inflammatory effects. The present study explored the possible protective effect of paeonol against HIR injury and investigated its possible molecular mechanisms in rats. Rats were randomly divided into four groups: sham-operated control, paeonol-treated sham-operated control, HIR untreated, and HIR paeonol-treated groups. The results confirmed that hepatic injury was significantly aggravated biochemically by elevated serum levels of alanine transaminase and aspartate transaminase, as well as by histopathological alterations, while paeonol reduced the increase in transaminases and alleviated pathological changes induced by HIR. Additionally, paeonol inhibited the HIR-induced oxidative stress in hepatic tissues by decreasing the upraised levels of malondialdehyde and nitric oxide and enhancing the suppressed levels of reduced glutathione and superoxide dismutase activity. Furthermore, paeonol activated the protective antioxidative Nrf2/HO-1 pathway. The protective effect of paeonol was associated with inhibiting the expression of the inflammatory key mediators TLR4, MYD88, NF-κB, and TNF-α. Finally, paeonol inhibited the increased mRNA levels of the pro-apoptotic marker Bax and enhanced the reduced mRNA levels of the anti-apoptotic marker Bcl-2. Taken together, our results proved for the first time that paeonol could protect against HIR injury by inhibiting oxidative stress, inflammation, and apoptosis.